ANALISIS KESIAPAN KABUPATEN KUTAI KARTANEGARA DALAM MENERAPKAN SMART CITY - Adisaputra, Wahyu Agung; Suwarjo, Suwarjo (POPULIKA, 2023)
The selection of Kutai Kartanegara Regency as 1 of 25 regions in implementing the work program of the 100 Smart City Movement based on the Republic of Indonesia Ministry of Communication and Information Decree Number 265.KOMINFO/DJAI/AI.01.05/05/2017, is both an opportunity and a challenge to make this happen. This study aims to analyze the readiness of Kutai Kartanegara Regency in implementing Smart City in several dimensions. This study used a qualitative descriptive approach with informants from implementers at the Office of Communication and Information and Bappeda of Kutai Kartanegara Regency. Triangulation is used to test the validity of the data. The results of the study show that the dimensions of Smart City development in Kutai Kartanegara Regency which include smart governance, smart branding, smart economy, smart living, smart society and smart environment have been supported by several aspects. From the superstructure aspect, Smart City development is based on the vision and mission of Kutai Kartanegara Regency so that it has a strong basis to be realized. From a structural aspect, it is supported by Regional Apparatus Organizations (OPD), BUMN, BUMD and the formation of Creative Economy Committees in the regions. From the infrastructure aspect, it is carried out through the provision of internet networks and various digital applications. From the aspect of community readiness, efforts have been made to support the development of an internet network with equitable access. From the aspect of hilly nature, extensive forests and many rivers are still obstacles to equal distribution of internet network access and adequate road access. Keywords: Smart City, Smart Regency Kutai Kartanegara, Regional Readiness Analysis